(untitled) (Eurasian Medical Research Periodical, 2022)
The aim of this research was to extract a significant amount of biosurfactant on an industrial scale from a local isolation of Lactobacillus acidophillus. This assignment was assigned to a 7L laboratory bioreactor, and all production parameters were established using batch culture experiments. At 30oC and 6.5 pH, a bioreactor with a working volume of 3.5 L was run for 120 hours to achieve 32 g/L. The manufacturing medium’s supernatant was employed to lower water’s surface tension from 72 to 24 mN/m, resulting in a 57 percent emulsification activity. The product was extracted with a variety of solvents and purified on a silica gel column (3.5 x 30cm) using glass chromatography. The toxicity of BS against breast cancer (AMJ-13) cell line was found to be 23%. When BS was used with antibiotics to treat pathogenic clinical isolates, it was discovered that ampicillin and tetracycline have a synergistic effect against S. aureus and E. coli.